(untitled) (Journal of Science Foundation, 2019)
Background: The clinical profiles and urinary albumin are very important for the prediction of preeclampsia among the pregnant women. Objective: The purpose of the present study was to assess the clinical and demographic profiles as well as the urinary albumin for the prediction of preeclampsia among the pregnant women. Methodology: This cohort study was conducted in the OPD of the Department of Obstetrics and Gynaecology at Rajshahi Medical College Hospital, Rajshahi, Bangladesh from January 2013 to December 2014 for a period of two (2) years. This study was carried on pregnant woman attending in outdoor department of Gynaecology, Rajshahi Medical College Hospital, Rajshahi, Bangladesh before 20th weeks of pregnancy who were healthy normotensive primigravidae with singleton pregnancy. The details demographic profiles, edema were collected from the study population. Urinary albumin was estimated before 20th weeks and after 28th weeks of pregnancy. Result: In the present study, 75 women were included; all were before 20th weeks of pregnancy without any complication or any risk factor for developing PE. Among the study group incidence of PE was 16%. The population are 24(32.0%) low, 31(41.3%) middle and 20(26.7%) high in socio economic conditions. Education level of study population was 45% completed primary education level, illiterate (27%) and secondary education (28%). Edema was absent in 1st visit, in 2nd visit 6(+), 6(++) present who developed PE, 18(+) present who did not develop PE. Edema was absent in 1st visit and (+) 6(50.0%) and (++) in 6(50.0%) present who developed PE in 2nd visit. Urine albumin in 1st visit nil in 6(50.0%), trace in 3(25.0%) and (+) in 3(25.0%) who developed PE. Conclusion: In conclusion housewife living in urban area in middle income socioeconomic condition are the most commonly presented with preeclampsia and urinary albumin is the most commonly detected in the pregnant women presented with preeclampsia Journal of Science Foundation 2018;16(2):54-59